The Theatre, Posters and Comics in Galicia in the 1970s - Oti Ríos, Francisco (Madrygal. Revista de Estudios Gallegos, 2016)
In this essay we can find the relationship between theatre and graphic art through the study of posters and brochures published for theatrical performances in Galicia during the 1970s and 1980s. During this time, artists and intellectual supported the political and cultural changes that were emerging at the end of Franco’s regime. It was a time when society underwent a labour movement and saw the legalization of political parties along with the abolition of censorship. All this gave rise to a new structure of the Galician theatrical system and the birth of the Galician comic.
Keywords: Galicia; Theatre; Posters; Comics; Performing Arts; Graphic Arts.